Anatomic Flat Double-Bundle Medial Collateral Ligament Reconstruction - Janina Kaarre, M.D., M.Sc.; Armin Runer, M.D.; Neilen A. Benvegnu, M.D.; Sahil Dadoo, B.S.; Fabian Persson; Michael Nammour, M.D.; Volker Musahl, M.D.; Kristian Samuelsson, M.D., Ph.D., M.Sc. (Arthroscopy Techniques, 2023)
Several surgical techniques have been described to restore the anatomy of the medial collateral ligament, involving suture repair and reconstruction, with the latter having been associated with superior postoperative outcomes. Recently, a growing interest in anatomic isometric medial collateral ligament reconstruction (MCLR) has been developed, involving careful evaluation and finding the most appropriate location for the femoral placement of the allograft. Therefore, the purpose of this article is to describe anatomic MCLR aiming to restore medial knee stability by focusing on isometric positions within the native anatomy of the MCL.